Eksistensi Harta dalam Persepsi Jamaah Tabligh Gorontalo - Muhibbuddin Muhibbuddin (Al-Mizan (e-Journal), 2020)
The tabligh community is one of the Islamic organizations that exist and grow in Indonesia. This community spreads throughout the world because each country has a headquarters that will coordinate the tabligh congregation movement. In understanding and addressing the use of assets, the tabligh congregation adheres to the philosophy that has been guided by their great leader in India. First, the assets obtained are set aside as optimally as possible for da'wah (khuruj) trips. They have to save and try to raise funds before leaving for preaching. Second, the attitude of sharing empathy to help the family left by her husband to preach. Striving for joint funds and deliberation on the assessment of family needs is done until a predetermined period of confusion. Third, wealth is used to make the Great Assembly successful in gathering the dai's. Fourth, distribute zakat and other social funds. Fifth, trying to live zuhud. Maximizing the acquisition of assets and living inadequate conditions. Not too chasing to pile up treasures, let alone go wild. Fourth, avoiding redundant behavior, either when making a da'wah visit or while being staying, standing in one's own village. Trained when doing da'wah trips by utilizing funds optimally to support the needs of the group of jamaah.